PROSPEK PERDAGANGAN INDONESIA, CINA DAN INDIA MELALUI ANALISA GRAVITY MODEL - Pakasa Bary (Buletin Ilmiah Litbang Perdagangan, 2010)
Global growth has shrunk affected by 2008 global financial crisis, especially contributed by advanced economies that experienced strongest decline. Indeed, it also affected their production and their demand of inputs, and hence decreased exports of countries providing upstream commodities. Meanwhile, China and India record a remarkable growth and only slightly affected by the crisis. Consistently, percentage of Indonesian exports to China and India, especially raw commodities, has been rising since 2008, and likely to increase furthermore in the future. This paper applies simple gravity model to evaluate the sensitivity of productions or income of these three economies on Indonesian exports to China and India. Using various methods and assumptions, estimation results suggest strong sensitivity of importers’ income and production. Indeed, it is likely that Indonesian exports to China and India will increase furthermore and hence boosting Indonesia economic growth along with China and India, making them the next growth triangle in Asia. While China nowadays is the strongest demand source for Indonesian exports, India may be the significant contributor in the near future. Nevertheless, there still must be significant reform in trade barriers and domestic economic strategy to support this potency in globalized world.